The role of kindergarten educators in developing the concept of tolerance among kindergarten children from their point of view (A field study in the city of Lattakia) - درويش, سمر; مطيعة أحمد, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of the current research is to know the role of kindergarten educators in developing the concept of tolerance for kindergarten children from their point of view, The research sample consisted of (100) educators from private kindergartens in the city of Lattakia for the academic year 2021/2022. The researcher adopted the descriptive approach, and used the questionnaire as a research tool, which was designed by her and judged by a group of specialists, Its stability was confirmed by applying it to a pilot sample that included (34) a kindergarten educator from outside the research sample, By calculating the alpha-Cro-Nbach coefficient, which reached (0.951). The research reached the following: -The role of kindergarten educators in developing the concept of tolerance among kindergarten children came to a high degree. -There are no statistically significant differences in the views of kindergarten educators about their role in developing the concept of tolerance in the child according to the variable number of years of experience for the educator. - There are no statistically significant differences in the views of kindergarten educators about the items of the questionnaire about their role in the concept of tolerance in the child according to the educator's educational and educational qualification variable.